Sounding others' sensations in interaction. Issue 1 (2nd January 2023) - Keevallik, Leelo; Hofstetter, Emily; Weatherall, Ann; Wiggins, Sally
ABSTRACT: This study investigates the practice of "sounding for others, " wherein one person vocalizes to enact someone else's putatively ongoing bodily sensation. We argue that it constitutes a collaborative way of performing sensorial experiences. Examples include producing cries with others' strain or pain and parents sounding an mmm of gustatory pleasure on their infant's behalf. Vocal sounds, their loudness, and duration are specifically deployed for instructing bodily experiences during novices' real-time performance of various activities, such as tasting food for the first time or straining during a Pilates exercise. Vocalizations that are indexically tied to the body provide immediate displays of understanding and empathy that may be explicated further through lexicon. The existence of this practice challenges the conceptualization of communication as a transfer of information from an individual agent – even regarding assumedly individual body sensations – instead providing evidence of the joint nature of action and supporting dialogic theories of communication, including when language-marginal vocalizations are used.